Impact and Adaptation to Climate Change in the agricultural sector for water and food security - Kumar, Rohitashw; Gautam, Harendra Raj (Indian Farming, 2015)
It is a reality now that climate is changing and measures are to be taken to do something about its impact on agriculture. Policy makers and Scientists at the international and national level have been suggesting certain measures to be followed to adapt to the climate change, which has to be taken up seriously. Good farming practices need to be promoted that are compatible with changing climatic conditions. Water management and water storage practices is also an important aspect to be considered as it forms an essential part of the agriculture sector.